The effect of periodontal therapy on glycaemic control in a Hispanic population with type 2 diabetes: a randomized controlled trial. (1st June 2014) - Gay, Isabel C.; Tran, Duong T.; Cavender, Adriana C.; Weltman, Robin; Chang, Jennifer; Luckenbach, Estelle; Tribble, Gena D.
Abstract Objective In the Mexican–American population, the prevalence of Type 2 diabetes mellitus (T2DM) is as high as 50% of the population. This randomized controlled clinical trial was designed to elucidate how treatment of periodontal disease affects HbA1c values in this population. Materials and Methods One hundred and fifty‐four T2DM patients with periodontal disease were enrolled in the study. The test group was treated with scaling and root planing (SRP); the control group received oral hygiene instructions. At baseline and 4–6 weeks after therapy, a complete periodontal examination was performed. Blood was collected at baseline and 4 months later for HbA1c levels. Results One hundred and twenty‐six individuals completed the study. Baseline mean ± SD HbA1c for the test and control groups were 9.0 ± 2.3% and 8.4 ± 2.0% respectively. Non‐significant difference in HbA1c reductions (0.6 ± 2.1% and 0.3 ± 1.7%) was found between test and control groups at 4 months. Comparisons of the periodontal clinical parameters between the test and control groups found significant differences with improved results in the test subjects. Conclusions No statistically significant differences were found in the changes of HbA1c levels between test and control groups. Non‐surgical periodontal therapy improved the magnitude of change in periodontal parameters as compared to the control subjects. ClinicalTrials.gov Identifier: NCT01128374